Clinical and molecular features of the hereditary mixed polyposis syndrome. - Whitelaw, S; Murday, V; Tomlinson, I; Thomas, H; Cottrell, S; Ginsberg, A; Bukofzer, S; Hodgson, S; Skudowitz, R; Jass, JR; Talbot, I; Northover, J; et al. (1997)
BACKGROUND and AIMS: Various inherited syndromes predispose to the development of colonic juvenile polyps and colorectal cancer, with potential importance for sporadic tumorigenesis. This study describes features of a possibly new syndrome of atypical juvenile polyps and other colonic tumors and compares these features with those of known gastrointestinal tumor syndromes. METHODS: A large family, St. Mark's family 96, with a tendency to develop colonic polyps of mixed histological types is described. Genetic linkage to known polyposis syndromes has been tested. RESULTS: Adenomatous and hyperplastic polyps occur in affected members of the family, although the characteristic lesion is an atypical juvenile polyp. Some affected individuals have developed polyps of more than one type, and individual polyps may contain features of more than one histological type. Polyps can undergo malignant change. Typically, fewer than 15 polyps are found at colonoscopy and there is no extracolonic disease associated with the development of polyps. The family's polyps seem to be inherited in an autosomal-dominant fashion, but the disease is probably unlinked to candidate loci with importance in colorectal tumorigenesis, such as APC, hMSH2, and hMLH1. CONCLUSIONS: We term this family's disease hereditary mixed polyposis syndrome (HMPS). Although mutations in the putative HMPS gene may be responsible for syndromes such as juvenile and Peutz-Jeghers polyposes, HMPS may also be a distinct disease.